Tourism Development Strategy in Improving the Community Economy at Tanjung Bira Beach, Bonto Bahari District, Bulukumba Regency - Megawati Megawati; Thamrin Tahir; Muhammad Hasan; Muhammad Dinar (Pinisi Journal of Entrepreneurship Review, 2023)
This research is motivated by the development of the times that many tours are found in the Bonto Bahari District area, of course, there needs to be a special strategy carried out as an effort to remain competitive with other existing tours. With the existence of Tanjung Bira Beach tourism, of course, it can have a positive and negative impact on the economy of the people on Tanjung Bira Beach. The purpose of this study is to describe the tourism development strategy in improving the community's economy at Tanjung Bira Beach, describe the impact of tourism development at Tanjung Bira Beach in improving the community's economy, and describe the obstacles faced in developing tourism at Tanjung Bira Beach and the solutions taken. The results of this study indicate that: (1) Tourism development strategies in improving the economy of the surrounding community in the form of adding objects of attraction, developing accessibility, amenity, public facilities, institutions, and the potential that tourism objects already have with facilities and infrastructure that are already owned. (2) The impact of tourism development is income from foreign exchange, additional community income, additional government revenue, opening up jobs, multiplier effects, utilization of facilities by local communities, and no negative impact. (3) The obstacles faced in the development of tourism on Tanjung Bira beach are limited funds, lack of creativity of managers, and lack of cohesiveness or community involvement. The solution is in the form of regular evaluations, and receiving suggestions from visitors regarding development and what needs to be developed again.